COASTAL AQUIFER GROUNDWATER MODELING IN THE SOUTHERN PART OF YOGYAKARTA AREA, INDONESIA - Doung Rata; Doni Prakasa Eka Putra; Heru Hendrayana (Journal of Applied Geology, 2015)
Parangtritis beach, located in a coastal aquifer at the southern part of Yogyakarta Province, Indonesia is bounded by the Indian Ocean at the South, Opak River at the West, and Tertiary Limestone Rock to the East. Local land-use is predominantly agriculture, rice fields and settlements and the population is estimated to be 9,386 persons as per the 2012 census. The total surface area is estimated at 9.46 km2. The aims of this research were to understand the system of groundwater and to assess and predict saltwater intrusion by conducting a numerical groundwater model. Hydrological and hydrogeological data were collected directly from the field and from previous work for input into the model. The model simulates an unconfined aquifer system where the aquifer thickness varies from 30-40 meters. The material of the aquifer consists of sand varying from fine to coarse grain size and fine gravel with hydraulic conductivity values of 8.974 × 10−4, 1.794 × 10−3, and 1.337 × 10−3 m/s at the northern, central, and southern part of the research area, respectively. The maximum length of the saltwater interface was estimated at about 205.1 m laterally and 40 m vertically relative to the location of the groundwater table around 1m above sea level. Direction of groundwater flow is from north to south. Groundwater table elevation equals 5 m at the north and 0 m at the south with a hydraulic gradient estimated at about 2.45 × 10−3. As a result of a steady-state simulation as well as two cases of prediction for five and ten years in the future, it is determined that that the salinity of the surrounding environment is not potentially adverse to the groundwater quality in the study area. This is in part due to low population in this area and abundant groundwater resources, as well as the results of the groundwater model. Keywords: Coastal aquifer, numerical groundwater model, conceptual model, observed heads